Non-pharmacological Interventions for Postoperative Pain Management after Benign Prostatic Hyperplasia Surgery: A Systematic Review - Setyawan, Dwie Andrie; Nani, Desiyani (Universitas Muhammadiyah Semarang, 2026)
Benign prostatic hyperplasia (BPH) affects aging men. Transurethral resection of the prostate (TURP) represents the standard surgical management for moderate to severe conditions. Postoperative pain remains a significant clinical problem. Conventional analgesic management demonstrates adverse effects. Variable patient responses remain evident. Non-pharmacological strategies require evaluation. This systematic review evaluates the effectiveness of non-pharmacological nursing interventions in postoperative pain management following BPH surgery. A systematic search was conducted in PubMed, Scopus, Web of Science, CINAHL, and Cochrane CENTRAL. The publication period is from January 2017 to December 2024. Inclusion criteria comprised randomized controlled trials, quasi-experimental studies, adult patients undergoing BPH surgery, non-pharmacological interventions, and pain outcomes using validated instruments. PRISMA 2020 guidelines guided study selection. Joanna Briggs Institute appraisal tools assessed methodological quality. Narrative synthesis was applied due to heterogeneity. A total of 1,086 records were identified. Ten studies met inclusion criteria. Seven randomized controlled trials. Three quasi-experimental studies. Interventions included relaxation techniques, transcutaneous electrical acupoint stimulation, acupuncture, pranic healing, enhanced recovery after surgery protocols, and integrative approaches. Relaxation techniques reduced pain intensity (p < 0.001). Transcutaneous electrical acupoint stimulation decreased catheter-related bladder discomfort and reduced analgesic consumption. Acupuncture demonstrated sustained improvement in chronic pelvic pain (p < 0.001). Enhanced recovery after surgery protocols reduced catheterization duration and decreased early postoperative pain. Evidence quality ranged from moderate to high. Non-pharmacological nursing interventions demonstrate effectiveness in postoperative pain reduction. Improved recovery outcomes observed. Further multicenter trials required. The development of standardized clinical guidelines is recommended.